Alive in the nuclear age vol.1 .
An interview with Canadian and Soviet youths about nuclear weapons, Japanese who experienced the Hiroshima bombing, etc. it also presents footages on World War I and II, invention of the first atomic bomb and Canada's nuclear technology.